Hambatan Pembelajaran Rasm Usmani di Perguruan Tinggi Islam: Kajian Pustaka dan Model Pembelajaran Terpadu: Challenges in Teaching the Uthmanic Script at Islamic Higher Education Institutions: A Literature Review and an Integrated Learning Model - Muhammad Abdul Ghafur; Agusman Armansyah; Hasan Luthfy Attamimy; Deddi Effendi; Hilman Rosidi; Rizki Aminullah (Al-Ma‘ani: Journal of Islamic Studies, 2026)
Learning Rasm Usmani in Islamic Higher Education (PTKI) holds a strategic position as it directly relates to the accuracy of writing, reading, and copying Qur'anic texts. However, students frequently encounter conceptual, linguistic, technical, methodological, and reference-related learning barriers. This article aims to analyze the forms of these learning obstacles and formulate an integrated strategy applicable to lecturers and department management. This study employs a library research method by reviewing reputable journal articles, textbooks, official guidelines from the Ministry of Religious Affairs/LPMQ, curriculum documents (Syllabus/RPS), and academic papers published between 2016 and 2026. Data were analyzed through reduction, thematic classification, synthesis, and conceptual interpretation. The findings present a novelty in the form of an Integrated Learning Model of Rasm Usmani, which incorporates initial Qur'anic literacy diagnostics (BTQ), the use of visual comparative mushaf learning materials, curated digital media integration, and a practical 16-session curricular framework.